Iron–Nitrogen Coordination in Modified Graphene Catalyzes a Four‐Electron‐Transfer Oxygen Reduction Reaction. Issue 5 (26th February 2014) - Kamiya, Kazuhide; Koshikawa, Hiroyuki; Kiuchi, Hisao; Harada, Yoshihisa; Oshima, Masaharu; Hashimoto, Kazuhito; Nakanishi, Shuji
Abstract It is shown that iron–nitrogen (Fe/N) coordination in an Fe/N‐modified graphene (Fe/N‐graphene) electrocatalyst catalyzes a four‐electron transfer oxygen reduction reaction (ORR). The Fe/N‐graphene is synthesized by heat‐treating graphene oxides in the presence of an Fe/N complex at 900 °C for just 45 s. When the heat‐treatment period is increased, the Fe/N coordination bonds are broken and the number of electrons involved in the ORR decreases. Extended X‐ray absorption fine structure analysis and X‐ray absorption spectroscopy (XAS) show that both a complete sp2 graphitic structure and a high density of Fe/N coordination structures exist in the Fe/N‐graphene material, which is in contrast to the carbon‐based catalyst prepared by using the conventional pyrolysis method. XAS analysis also reveals that back‐donation from Fe atoms coordinated with N to an O antibonding π* orbital occurrs, promoting the four‐electron transfer ORR.